Virtual versus In-Person Ophthalmology Interviews: Perceptions of U.S. Ophthalmology Fellowship Applicants in 2022–2023 - Cherkas, Elliot G.; Shields, Charlotte N.; Mandava, Nikhil; Zhang, Lily; Sivalingam, Arunan; Kaiser, Richard S.; Myers, Jonathan S.; Hammersmith, Kristin M.; Razeghinejad, Reza; Finklea, Brenton D.; Shields, Carol L.; Sridhar, Jayanth; Wills Fellowship Study Group; Klufas, Michael A. (Journal of Academic Ophthalmology, 2023)
Purpose Despite easing restrictions on social distancing and travel since the beginning of coronavirus disease 2019 pandemic, virtual interviews remain a widely used format for ophthalmology fellowship interviews. This study aims to evaluate the relative benefits and drawbacks of in-person versus virtual interviews during a cycle where both formats were prevalent.Methods A prospective cross-sectional study surveyed all fellowship applicants (N = 311) who applied to Wills Eye Hospital and Bascom Palmer Eye Institute during the 2022 to 2023 application cycle.Results A total of 59 (19%) applicants responded to the survey, with the majority being male (53.0%) and between the ages of 20 and 35 (91.3%). There was no statistically significant difference between the number of virtual and in-person interviews attended or the total number of interviews attended. The highest ranked limitations of the virtual interview process were limited exposure to details of the program structure, limited opportunity to exhibit applicants' strengths to the program, and limited exposure to the fellows. The highest ranked strengths were less pressure during interviews, greater scheduling flexibility, and ability to interview at more fellowship programs. The highest ranked limitations of the in-person interview process were more pressure during interviews, inability to interview at all desired fellowship programs, and decreased scheduling flexibility. The highest ranked strengths based on median rankings were greater exposure to details of the program structure, greater ability to exhibit an applicant's strengths to the program, and greater exposure to the geographic location/city.Conclusion While both in-person and virtual interviews have their own benefits and limitations, virtual interviews appear to be more cost-effective and time-efficient while in-person interviews provide better opportunities to assess program fit and culture. A hybrid format that combines the ideal aspects of both formats may be an optimal solution.
Keywords: COVID-19; ophthalmology trainees; virtual interviews; medical education